2017
DOI: 10.1152/ajplung.00518.2016
|View full text |Cite
|
Sign up to set email alerts
|

Nonantibiotic macrolides restore airway macrophage phagocytic function with potential anti-inflammatory effects in chronic lung diseases

Abstract: We reported defective efferocytosis associated with cigarette smoking and/or airway inflammation in chronic lung diseases, including chronic obstructive pulmonary disease, severe asthma, and childhood bronchiectasis. We also showed defects in phagocytosis of nontypeable (NTHi), a common colonizer of the lower airway in these diseases. These defects could be substantially overcome with low-dose azithromycin; however, chronic use may induce bacterial resistance. The aim of the present study was therefore to inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 28 publications
1
52
0
1
Order By: Relevance
“…In the spinal cord injury patient population, for example, AZM is the antibiotic of choice for treating recurrent respiratory infections and pneumonia, a leading cause of death following spinal cord injury; thus, antibiotic resistance is a major concern. Fortunately, recent studies have indicated that macrolides modified to remove their antibacterial activity retain beneficial anti‐inflammatory effects in models of inflammatory skin disorders and chronic lung diseases …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the spinal cord injury patient population, for example, AZM is the antibiotic of choice for treating recurrent respiratory infections and pneumonia, a leading cause of death following spinal cord injury; thus, antibiotic resistance is a major concern. Fortunately, recent studies have indicated that macrolides modified to remove their antibacterial activity retain beneficial anti‐inflammatory effects in models of inflammatory skin disorders and chronic lung diseases …”
Section: Discussionmentioning
confidence: 99%
“…After 30 minutes, 10 mL of methanol and 10 mL saturated (d, J = 6.6 Hz, 3H), 0.87 (dd, J = 8.4, 6.5 Hz, 3H). 13 0.99 (dd, J = 13.7, 6.9 Hz, 3H), 0.88 (q, J = 7.5 Hz, 3H). 13…”
Section: Semisynthesis Of Azm Derivativesmentioning
confidence: 99%
See 2 more Smart Citations
“…Some of this phagocytosis is likely mediated by efferocytosis (Akbar et al, 1994). Because Mer has been shown to be expressed on human monocytes and tissue macrophages, including alveolar macrophages, macrophages in the liver and in mesenteric lymph nodes, and microglia (Bernsmeier et al, 2015; Zhu et al, 2014; Hodge et al, 2017; Kazeros et al, 2008; Healy et al, 2016), it would be of interest to investigate whether PtdSer/protein S/Mer mediates efferocytosis of SIV and/or HIV-1-infected cells and contributes to the amounts of viral DNA and proteins detected in macrophages in vivo .…”
Section: Discussionmentioning
confidence: 99%